The super-short Dark Tetrad: Development and validation within the Chinese context. (April 2022) - Meng, Xue; Li, Chaoping; Liu, Doudou; Xu, Yan
Abstract: In the past decades, the Dark Triad traits have gained research attention. These traits include Machiavellianism, narcissism, and psychopathy. A growing consensus is that sadism should also be included in these traits. To include the additional trait, the short Dark Tetrad (SD4) scale was developed. In the present study, the 28-item SD4 was translated into Chinese and revised into a super-short version. In two large samples (total N = 898), the 16-item super-short Dark Tetrad (SSD4) presented the following characteristics: (1) favorable reliability estimates and item properties; (2) a bifactor structure; (3) factorial invariance across groups by gender, age, and education level; (4) adequate validity by correlations with aggression, self-esteem, counterproductive work behavior, and life well-being; and (5) high convergent correlations with the SD4. Overall, our results suggest that the SSD4 is a reliable and concise measure that could be used in future research. Highlights: The super-short Dark Tetrad produces sound psychometric properties. The scale is reliable within the Chinese context. The super-short Dark Tetrad shows a bifactor structure. Factorial invariance across groups by gender, age, and education level was observed.